(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The idea of expressing certain kind of numbers as linear combination of special class of numbers has always been an interesting exercise in mathematics. In this paper, I present an interesting way to write a given natural number as sum or difference of integral powers of golden ratio, silver ratio and bronze ratio. Suitable illustrations enabling the process are briefed in the paper.